2015
DOI: 10.3892/ol.2015.3417
|View full text |Cite
|
Sign up to set email alerts
|

High expression levels of unc-51-like kinase 1 as a predictor of poor prognosis in colorectal cancer

Abstract: Abstract. Colorectal cancer (CRC) is one of the most common and lethal cancers worldwide. Unc-51-like kinase 1 (ULK1) plays an important role in autophagy, which is widely involved in human CRC. The aim of the present study was to investigate the clinical and prognostic significance of the expression of ULK1 in human CRC. Expression of ULK1 in 339 CRC specimens (tumor-node-metastasis stages I-IV) was assessed by immunohistochemistry. The optimal cutpoint of the expression of ULK1 was assessed by the X-tile pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
17
1
1
Order By: Relevance
“…In breast cancer [40] and gastric cancer [43], high expression of ULK-1 appears to associate to good patient prognosis. This contradicts the findings in colorectal cancer [44]. A separate study in colorectal cancer did not demonstrate any correlation to survivability, even after taking into account the status of KRAS.…”
Section: Ulk-1/ulk-2contrasting
confidence: 72%
“…In breast cancer [40] and gastric cancer [43], high expression of ULK-1 appears to associate to good patient prognosis. This contradicts the findings in colorectal cancer [44]. A separate study in colorectal cancer did not demonstrate any correlation to survivability, even after taking into account the status of KRAS.…”
Section: Ulk-1/ulk-2contrasting
confidence: 72%
“…Ulk1 is overexpressed in NSCLC cell lines. It has been reported that in several cancers, such as breast cancer, colorectal cancer, esophageal squamous cell carcinoma and human nasopharyngeal carcinoma, Ulk1 is upregulated and is negatively correlated with prognosis, but the role of Ulk1 in NSCLC remains unclear (12)(13)(14)(15)(16)). In the current study, the expression of Ulk1 was tested in five NSCLC cell lines (A549, H292, H460, H1299 and HCC827) and one normal human lung cell line (BEAS-2B).…”
Section: Resultsmentioning
confidence: 99%
“…Pike et al showed that Ulk1 promotes cell survival of several cancers (12). Moreover, overexpression of Ulk1 has been shown to be negatively correlated with the prognosis of a variety of cancers, such as colorectal cancer, breast cancer, human nasopharyngeal carcinoma and esophageal squamous cell carcinoma (12)(13)(14)(15)(16). Egan et al reported that the compound SBI0206965, a highly selective kinase inhibitor of Ulk1 both in vitro and in vivo, suppresses Ulk1-mediated phosphorylation events in cells and prevents Ulk1-dependent cell survival by suppressing autophagy (5).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, overexpression of ULK1 plays an oncogenic role in most of tumor types, including hepatocellular carcinoma [208], esophageal squamous cell carcinoma [209], nasopharygeal carcinoma [210] as well as colorectal cancer [211], which predicts poorer prognosis and severer progression. In addition, the protective autophagy induced by ULK1 is observed among mice with xenograft prostate cancer, thus preventing apoptosis and triggering neoplastic advancement [212].…”
Section: Functions Of Ampk Signaling Components In Tumorigenesismentioning
confidence: 99%